Temporal-spatial Parameters for Urban Rail Transit Train Coupling and Decoupling Operations Based on Virtual Coupling Technology - XIAO Liweining; BAI Yun (Chengshi guidao jiaotong yanjiu)
[Objective] In response to the growing pressure of urban rail transit passenger flow, train virtual coupling technology possesses significant advantages in enhancing urban rail transit train operation efficiency, alleviating constraints on line transport capacity, and adapting to uneven spatial and temporal distribution of passenger flow. It is thus necessary to study its specific temporal-spatial parameters. [Method] Based on the conventional safety braking model, a train safety braking model for virtually coupled train formations in urban rail transit is established to calculate and derive the minimum safe distance between train units under ideal conditions. Building on this foundation and through simulation calculations, the temporal-spatial parameters under time-saving operation mode, such as train coupling and decoupling duration and zone length are obtained. Furthermore, a sensitivity analysis is conducted on two selected parameters: the time required to establish train-to-train communication and the maximum permissible speed between sections. [Result & Conclusion] Under identical train operating speeds, the minimum safe distance between trains in virtually coupled train units is significantly smaller than that in traditional tracking modes, and the increase of train operating speed will cause an increase in the gap between them. When train operating speed is 60 km/h, the minimum safe distance between trains in the former shortens by 75.7% in comparison to the latter. The time required to establish train-to-train communication has a substantial impact on train coupling. With a train-to-train communication range of 30~60 seconds, the increment amplitude of train coupling duration and zone length goes up to 103.4% and 100.4%, respectively. Given that train operational safety is ensured, setting a higher maximum allowable interval speed is more conducive to the optimal curve running of train application, thereby shortening train coupling duration and zone length.